PENERAPAN METODE INQUIRY DALAM MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS VI SDN 002 NONGSA - Victoria, Victoria (Lentera: Jurnal Ilmiah Kependidikan, 2021)
This research is a classroom action research. It consists of several aspects of action and main observations, namely the improvement of student learning outcomes using the Inquiry method. The purpose of this study was to improve student learning outcomes in science learning at SDN 002 Nongsa by applying the inquiry method. The research was conducted at SDN 002 Nongsa, involving 35 students. This study used a research design by Kemmis and Mc. Taggart, which consists of two cycles. Where in each cycle a class meeting is held and each cycle consists of four stages, namely planning, implementing, observing, and reflecting. The results showed that in the action cycle I obtained 57.14% classical completeness and 71.43% classical absorption. In the second cycle of action, the classical completeness was obtained 85.71% and the classical absorption rate was 91.43%. This means that learning in cycle II has met the indicators of success with a minimum classical learning completeness value of 85% and casical absorption of 65%. Based on the average value of classical absorption and classical learning completeness in cycle II learning activities, it can be concluded that learning using the inquiry approach can improve student science learning outcomes at SDN 002 Nongsa.